Fossil ecosystems of North America a guide to the sites and their extraordinary biotas - Nudds, John R. (Manson, 2008)
Most major recent advances in understanding the history of life on Earth have been through the study of exceptionally well preserved biotas (Fossil-Lagerstätten). These are windows on the history of life on Earth and can provide a fairly complete picture of the evolution of ecosystems through time. This book follows the success of Evolution of Fossil Ecosystems by the same authors which covered Fossil-Lagerstätten around the world. The success of the first book prompted this new book which draws on four localities from the original book and adds another ten, all located in North America. Follow.